Ceftriaxone Therapy of Bacterial Meningitis in Children - Sumarmo Sumarmo; S. R. Harun; M. A. Nathin (Paediatrica Indonesiana, 1988)
Twenty-nine children, age 3 months to 11 years, admitted with the clinical diagnosis of bacterial meningitis to the Department of Child Health, were included in a prospective treatment study of ceftriaxone (RocephinHoffmann- La Roche AG Bas/e, Switzerland). Ceftriaxone was used as the only antibiotic agent in single daily dose of 100 mg/kg body weight given intravenously for a minimum of 10 days. Of these 29 patients, 25 (86.2%) recovered, 3 (10.3%) died and 1 (3.4%) no respond to treatment. Among fatal cases, two patients had subdural empyema and one had a cerebral abscess. The microorganisms isolated from cerebrospinal fluid were: Streptococcus pneumoniae (5), Pseudomonas sp. (4), Proteus sp. (2), Salmonella typhi (1), Escherichia coli (1), Clostridium sp. (1), Pseudomonas aeruginosa (1), Staphylococcus aureus {1), and Streptococcus haemolyticus (1). In 12 patients (41,4%), organisms were not identified. The diagnosis was made based on clinical symptoms, Gram staining, cell count. ~!Â·tease, and protein in the CSF. In all patients, repeated spinal fluid cultures had no bacterial growth at 24 hours after initation of intravenous therapy. No evidence of clinical important drug toxicity was observed. Three p'Oiients, however, had lightly elevated hepatic transaminase levels, and one patient had rnild neutropenia. These clinical and bacteriological results suggested that ceftriaxone is reasonably safe and effective in the treatment of bacterial meningitis caused by the most common pediatric pathogens in Indonesian children over one month of age.